Study of serum metabolic profiles of patients with non-small cell lung cancer with special emphasis on the smoking status of patients - Klupczynska, Agnieszka; Kasprzyk, Mariusz; Dyszkiewicz, Wojciech; Grabicki, Marcin; Batura-Gabryel, Halina; Kokot, Zenon J.; Matysiak, Jan (Journal of Medical Science, 2019)
The project entitled “Study of serum metabolic profiles of patients with non-small cell lung cancer with special emphasis on the smoking status of patients” is a study based on metabolomics, which is the latest of the “omics” technologies and involves a comprehensive analysis of small molecule metabolites of a specific biological sample. High-throughput and sensitive analytical techniques used in metabolomic investigations are powerful tools in the field of oncology and aids understanding what is happening in cancer cells and searching for new cancer markers. The aim of the project is to determine whether lung cancer patients have a distinct serum metabolic profile and whether this profile is associated with patients’ smoking status. The application of liquid chromatography-high-resolution mass spectrometry-based methodology along with advanced statistical methods will enable to select potential molecules that can be useful in early lung cancer detection.